2014
DOI: 10.1124/jpet.113.210005
|View full text |Cite
|
Sign up to set email alerts
|

G Protein–Coupled Bile Acid Receptor 1 Stimulation Mediates Arterial Vasodilation through a KCa1.1 (BKCa)–Dependent Mechanism

Abstract: Bile acids (BAs) and BA receptors, including G protein-coupled bile acid receptor 1 (GPBAR1), represent novel targets for the treatment of metabolic and inflammatory disorders. However, BAs elicit myriad effects on cardiovascular function, although this has not been specifically ascribed to GPBAR1. This study was designed to test whether stimulation of GPBAR1 elicits effects on cardiovascular function that are mechanism based that can be identified in acute ex vivo and in vivo cardiovascular models, to delinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 51 publications
(58 reference statements)
3
34
0
Order By: Relevance
“…Furthermore, alterations of BA metabolism have been found in cardiac disease and heart failure [30, 31, 53]. Recently, G-protein-coupled BA receptor-1 has been identified as central pathway in BA-mediated hemodynamic alterations [28, 29]. We observed a significant correlation of TC and TCDC with arterial blood pressure in our cohort.…”
Section: Discussionsupporting
confidence: 66%
“…Furthermore, alterations of BA metabolism have been found in cardiac disease and heart failure [30, 31, 53]. Recently, G-protein-coupled BA receptor-1 has been identified as central pathway in BA-mediated hemodynamic alterations [28, 29]. We observed a significant correlation of TC and TCDC with arterial blood pressure in our cohort.…”
Section: Discussionsupporting
confidence: 66%
“…BAs are directly vasoactive and induce splanchnic vasodilation by relaxing smooth muscle cells and may contribute to portal hypertension . Recently, stimulation of G‐protein‐coupled BA receptor‐1 was described as central pathway for inducing peripheral vasodilation via BAs . Furthermore, BA seem to directly activate inflammatory pathways in hepatocytes during cholestasis by stimulating production of proinflammatory mediators .…”
Section: Discussionmentioning
confidence: 99%
“…41,43 Recently, stimulation of G-protein-coupled BA receptor-1 was described as central pathway for inducing peripheral vasodilation via BAs. 47,48 Furthermore, BA seem to directly activate inflammatory pathways in hepatocytes during cholestasis by stimulating production of proinflammatory mediators. 49,50 Beside this, BA signalling aspects, via the nuclear receptor FXR as well as TGR5, modulate the whole bodies energy and metabolic regulation.…”
Section: Discussionmentioning
confidence: 99%
“…This results in gallbladder filling and volume expansion, which is a major obstacle in the clinical application of TGR5 agonists. In addition, impaired immune responses [14] and alterations in heart rate have been identified as side effects of TGR5 activation [15,16] . Recent research has demonstrated that TGR5 activation and subsequent GLP-1 secretion occur at the luminal…”
mentioning
confidence: 99%